Using Focus Groups to Listen, Learn, and Lead in Higher Education - Tory Dellafiora (University of Minnesota Libraries Publishing, 2021)
Using Focus Groups to Listen, Learn, and Lead in Higher Education is an excellent addition to the bookshelf of anyone looking to expand their research and assessment toolbelt. Danner, Pickering, and Paredes serve as excellent guides on the structured method to conducting focus groups that their institution has honed over the years. The resources, checklists, and reference materials in the back of the book alone are worth a read, as they provide structure and guidance to a process that may intimidate those unfamiliar with the implementation of focus groups on a college campus. The book is a quick and thorough read that allows one to feel prepared and equipped to use this method in their own research and assessment processes.